1995
DOI: 10.1136/ard.54.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Steroid induced osteoporosis: an opportunity for prevention?

Abstract: Objective-To determine the frequency with which osteoporosis prophylaxis is given to corticosteroid treated hospital inpatients. Methods-All patients receiving systemic corticosteroids in a large teaching hospital over a three month period were identified through routine prescription monitoring by hospital ward pharmacists. Coprescription of antiosteoporotic therapy was recorded, along with other relevant details such as steroid dose, actual, or intended duration of therapy, and indication for therapy. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
1
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 8 publications
5
36
1
2
Order By: Relevance
“…However, similar to findings in our prior study and other US and international studies (11,12,(20)(21)(22)(23)(24), we found low utilization rates and significant practice pattern variation between physician specialties in screening and preventive therapies for glucocorticoid-induced osteoporosis. We also found significant variation between prescribing physician specialties in the proportion of their patients taking OTC calcium or vitamin D supplements.…”
Section: Temporal Trends In Prevention Of Glucocorticoid-induced Ostesupporting
confidence: 90%
“…However, similar to findings in our prior study and other US and international studies (11,12,(20)(21)(22)(23)(24), we found low utilization rates and significant practice pattern variation between physician specialties in screening and preventive therapies for glucocorticoid-induced osteoporosis. We also found significant variation between prescribing physician specialties in the proportion of their patients taking OTC calcium or vitamin D supplements.…”
Section: Temporal Trends In Prevention Of Glucocorticoid-induced Ostesupporting
confidence: 90%
“…Compared with the findings among glucocorticoid users in the general population, [4][5]8 ophthalmology clinics, 13 medical wards 7,11 and medical outpatient clinics, 14 the results of this study suggest that rheumatology outpatients receiving glucocorticoids were more likely to have been offered bone density measurement and/or prophylactic treatment. It appears that practising rheumatologists have a generally higher level of awareness of glucocorticoid-induced osteoporosis and are more likely to evaluate risk and consider appropriate bone-sparing therapy.…”
Section: Discussioncontrasting
confidence: 47%
“…Previous studies have shown that the vast majority of glucocorticoid-treated patients have not been evaluated for osteoporosis risk or commenced on treatment to prevent accelerated bone loss and future fracture. [8][9][10][11][12][13][14][15] Rheumatologists are among those with the greatest experience of glucocorticoid therapy, and are also most likely to report that they would prescribe preventive therapy. 16 A survey of medical inpatients in Australia suggested that rheumatological patients taking glucocorticoids were more likely to have been offered bone density screening and/or prophylactic treatment than were similar patients with respiratory disease.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those from studies in other medical specialties in which bisphosphonates were rarely prescribed. [18][19][20][21] In a British study by Hart and Green, 19 bisphosphonates were prescribed at a rate of 21.6% for patients who qualified for GIOP prophylaxis. Two other studies from the United States showed that bisphosphonates were received by only 4% and 8% of patients, respectively, prior to the revision of the ACR guidelines.…”
Section: Commentmentioning
confidence: 99%